An audit of growth hormone replacement for GH‐deficient adults in Scotland. (12th March 2013) - Philip, Sam; Howat, Isobel; Carson, Maggie; Booth, Anne; Campbell, Karen; Grant, Donna; Patterson, Catherine; Schofield, Christopher; Bevan, John; Patrick, Alan; Leese, Graham; Connell, John
Summary Objective Guidelines on the clinical use of growth hormone therapy in adults were issued by the UK National Institute for Clinical Excellence (NICE) in August 2003. We conducted a retrospective clinical audit on the use of growth hormone (GH) in Scotland to evaluate the use of these guidelines and their impact on clinical practice. The audit had two phases. In phase I, the impact of NICE criteria on specialist endocrine practice in starting and continuing GH replacement was assessed. In phase II, the reasons why some adults in Scotland with growth hormone deficiency were not on replacement therapy were evaluated. Methods A retrospective cross‐sectional case note review was carried out of all adult patients being followed up for growth hormone deficiency during the study period (1 March 2005 to 31 March 2008). Phase I of the audit included 208 patients and phase II 108 patients. Results Sellar tumours were the main cause of GH deficiency in both phases of the audit. In phase I, 53 patients (77%) had an AGHDA‐QoL score >11 documented before commencing GH post‐NICE guidance, compared with 35 (25%) pre‐NICE guidance. Overall, only 39 patients (18%) met the full NICE criteria for starting and continuing GH (pre‐NICE, 11%; post‐NICE, 35%). Phase II indicated that the main reasons for not starting GH included perceived satisfactory quality of life (n = 47, 43%), patient reluctance (16, 15%) or a medical contraindication (16, 15%). Conclusions Although the use of quality of life assessments has increased following publication of the NICE guidelines, most adults on GH in Scotland did not fulfil the complete set of NICE criteria. The main reason for not starting GH therapy in adult GH‐deficient patients was perceived satisfactory quality of life.